2006
DOI: 10.2337/db05-1390
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Mediated Phosphorylation of the Proline-Rich Akt Substrate PRAS40 Is Impaired in Insulin Target Tissues of High-Fat Diet–Fed Rats

Abstract: Clinical insulin resistance is associated with decreased activation of phosphatidylinositol 3-kinase (PI3K) and its downstream substrate protein kinase B (PKB)/Akt. However, its physiological protein substrates remain poorly characterized. In the present study, the effect of in vivo insulin action on phosphorylation of the PKB/Akt substrate 40 (PRAS40) was examined. In rat and mice, insulin stimulated PRAS40-Thr246 phosphorylation in skeletal and cardiac muscle, the liver, and adipose tissue in vivo. Physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
44
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 25 publications
7
44
0
1
Order By: Relevance
“…Based on biochemical measurements, some have argued that defects in insulin signaling in muscle are late events seen after 30 but not after 8 weeks of high-fat diet (7). In contrast, other studies have reported reduced insulin-stimulated PI3-K and Akt/ protein kinase B activities after only 4 weeks of high-fat diet (5,37) and reduced Akt/protein kinase B signaling after 7 weeks of high-fat diet (38). Our study, for the first time, shows that 12 weeks of high-fat diet reduce PI3-K activity in the entire length of the T-tubules and, to a lesser extent, in sarcolemma (Figs.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Based on biochemical measurements, some have argued that defects in insulin signaling in muscle are late events seen after 30 but not after 8 weeks of high-fat diet (7). In contrast, other studies have reported reduced insulin-stimulated PI3-K and Akt/ protein kinase B activities after only 4 weeks of high-fat diet (5,37) and reduced Akt/protein kinase B signaling after 7 weeks of high-fat diet (38). Our study, for the first time, shows that 12 weeks of high-fat diet reduce PI3-K activity in the entire length of the T-tubules and, to a lesser extent, in sarcolemma (Figs.…”
Section: Discussionmentioning
confidence: 43%
“…Previous biochemical studies have found either normal (4,5) or reduced (6,37,39) overall GLUT4 content in muscle from high fat-fed animals, while GLUT4 translocation was reduced (4,5,7). One study using subcellular fractionation found completely abrogated insulin-stimulated GLUT4 translocation to both sarcolemma and T-tubules (38).…”
Section: Discussionmentioning
confidence: 99%
“…Since the integrity of the insulin signalling cascade in beta cells is responsible for preservation of beta cell mass and for insulin secretion [43], and since JNK inhibition affects IRS-1/AKT in peripheral tissues [13][14][15], we tested the effect of L-JNKI in human islet insulin pathway with our main focus on AKT and its substrates. Among those substrates, GSK-3B and p70S6K participate in the regeneration of beta cell mass via increased mitogenesis [44,45], while PRAS40 is also activated by insulin in peripheral tissues and is implicated in protection of neurons against ischaemic injury [46,47]. We found that JNK inhibition in human islets treated with either L-JNKI or SP600125 specifically stimulated the phosphorylation of AKT and GSK-3B (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…Disturbances in the insulin-mediated activation of the IRS1/PI3K/Akt pathway, which facilitates GLUT4-dependent glucose disposal in skeletal muscle, characterise insulin resistance [12]. The impaired activity of the IRS1/PI3K/Akt pathway also results in reduced insulinmediated phosphorylation of one of the most prominent Akt substrates, the proline-rich Akt substrate of 40 kDa (PRAS40), in skeletal muscle of humans with type 2 diabetes and rodents fed a high-fat diet [13][14][15]. PRAS40 is a component of mTORC1 [16,17].…”
Section: Introductionmentioning
confidence: 99%